Peculiarities of optical and structure characteristics of sapphire single crystals grown in Ar+CO atmosphere - Dan‘ko, A.Ya.; Tkachenko, V.F.; Sidelnikova, N.S.; Puzikov, V.M.; Nizhankovskiy, S.V. (Functional Materials, 2004)
Presented are the results of optical and X-ray structure investigations of sapphire crystals grown by the method of HOC in the protective (reducing) medium Ar+CO under a pressure of 10...800 torr. The dependence of the crystals structure perfection on the pressure of the medium is established. It is shown that high-temperature annealing may raise the structure perfection up to the level characteristic of the crystals grown under the conditions of high vacuum (10⁻⁴ torr). Correlation of the parameters which characterize the structure perfection, with the concentration of anionic vacancies in the crystals, allows to assume that at the growth of sapphire crystals in reducing media, vacancy mechanism may play a noticeable role in the process of formation of dislocations and low-angle dislocation boundaries. Представлены результаты оптических и рентгеноструктурных исследований кристаллов сапфира, выращенных методом ГНК в защитной (восстановительной) среде Ar + CO в интервале давлений 10...800 торр. Установлена зависимость структурного совершенства кристаллов от давления среды. Показано, что в результате высокотемпературного отжига совершенство структуры может быть повышено до уровня, характерного для кристаллов, выращенных в условиях высокого вакуума (10⁻⁴ торр). Корреляция параметров, характеризующих совершенство структуры, с концентрацией анионных вакансий в кристаллах позволяет предложить, что при выращивании кристаллов сапфира в восстановительных средах в процессе формирования дислокаций и малоугловых дислокационных границ заметную роль может играть вакансионный механизм. Представлено результати оптичних i рентгеноструктурних досліджєнь кристалів сапфіра, вирощених методом ГСК у захисному (відновному) середовищі Ar + CO в інтервалі тисків 10... 800 тор. Встановлено залежність структурної досконалості кристалів від тиску середовища. Показано, що в результаті високотемпературного відпалу досконалість структури може бути підвищена до рівня, характерного для кристалів, вирощених в умовах високого вакууму (10⁻⁴ тор). Кореляція параметрів, що характеризують досконалість структури, з концентрацією аніонних вакансій у кристалах дозволяє припустити, що при вирощуванні кристалів сапфіра у відбудовних середовищах у процесі формування дислокацій і малокутових дислокаційних границь помітну роль може грати вакансійний механізм.